The SIN3/RPD3 Deacetylase Complex Is Essential for G(2) Phase Cell Cycle Progression and Regulation of SMRTER Corepressor Levels. - Pile, L.A.; Schlag, E.M.; Wassarman, D.A. (Molecular and Cellular Biology, 2002)
The SIN3 corepressor and RPD3 histone deacetylase are components of the evolutionarily conserved SIN3/RPD3 transcriptional repression complex. Here we show that the SIN3/RPD3 complex and the corepressor SMRTER are required for Drosophila G(2) phase cell cycle progression. Loss of the SIN3, but not the p55, SAP18, or SAP30, component of the SIN3/RPD3 complex by RNA interference (RNAi) causes a cell cycle delay prior to initiation of mitosis. Loss of RPD3 reduces the growth rate of cells but does not cause a distinct cell cycle defect, suggesting that cells are delayed in multiple phases of the cell cycle, including G(2). Thus, the role of the SIN3/RPD3 complex in G(2) phase progression appears to be independent of p55, SAP18, and SAP30. SMRTER protein levels are reduced in SIN3 and RPD3 RNAi cells, and loss of SMRTER by RNAi is sufficient to cause a G(2) phase delay, demonstrating that regulation of SMRTER protein levels by the SIN3/RPD3 complex is a vital component of the transcriptional repression mechanism. Loss of SIN3 does not affect global acetylation of histones H3 and H4, suggesting that the G(2) phase delay is due not to global changes in genome integrity but rather to derepression of SIN3 target genes.